DNA barcoding insights into echinoderms from Situbondo Coral Reefs, East Java, Indonesia - ELSA DIANITA AULIA; FARID KAMAL MUZAKI; SANG-KYU LEE; JONG SEONG KHIM; JINSOON PARK (Society for Indonesian Biodiversity, 2025)
Abstract. Aulia ED, Muzaki FK, Lee S-K, Khim JS, Park J. 2025. DNA barcoding insights into echinoderms from Situbondo Coral Reefs, East Java, Indonesia. Biodiversitas 26: 3434-3445. Echinoderms are a key component of marine ecosystems, contributing to species richness and serving ecological functions. Given their importance, observing their diversity and ecology is essential. Despite the favorable coral reef conditions in Situbondo on Java Island, a comprehensive record of echinoderms has never been done. This research addresses this knowledge gap by collecting and identifying the species richness with morphology and molecular identification using the mitochondrial gene Cytochrome Oxidase I (COI) and 16S ribosomal RNA. Timed sampling for 40 minutes was carried out at intertidal reefs from depths between 0-5 m and in shallow reefs from 5-20 m, with a total of five sites. A total of 45 echinoderm species were identified, encompassing 6 Asteroidea, 5 Crinoidea, 8 Echinoidea, 15 Holothuroidea, and 11 Ophiuroidea. Of the 71 echinoderm samples collected, COI sequences were successfully amplified in 66% of the samples, while 16S rRNA sequences had a success rate of 53%. Notably, the COI sequences of five species and the 16S sequences of eight species were reported to GenBank for the first time, contributing to the expansion of publicly available reference data for echinoderm molecular identification. Furthermore, the present study highlights phylogenetic uncertainties based on maximum likelihood analysis of the COI sequences, particularly within two Asteroidea species and one Ophiuroidea species from the Ophiolepis clade. In addition, the findings suggest a potential range extension for Diadema clarki (Ikeda, 1939), indicating previously undocumented distribution patterns. These findings provide essential baseline data and monitoring for future marine biodiversity research, especially considering the area's significant coastal water utilization for tourism and fishing activities.